Amino‐Acid‐Based Polymerizable Surfactants for the Synthesis of Chiral Nanoparticles. Issue 17 (27th June 2016) - Preiss, Laura C.; Wagner, Manfred; Mastai, Yitzhak; Landfester, Katharina; Muñoz‐Espí, Rafael
Abstract : Amino‐acid‐based chiral surfactants with polymerizable moieties are synthesized, and a versatile approach to prepare particles thereof with a chiral surface functionality is presented. As an example of an application, the synthesized particles are tested for their ability as nucleating agents in the enantioselective crystallization of amino acid conglomerate systems, taking rac ‐asparagine as a model system. Particles resulting from chiral surfactants with different tail groups are compared and the results demonstrate that only the chiral nanoparticles made of the polymerizable surfactant are able to act efficiently as nucleation agent in enantioselective crystallization. Abstract : Amino‐acid‐based chiral surfactants with polymerizable moieties are synthesized and polymer nanoparticles with a chiral surface functionality are prepared thereof. The nanoparticles are applied as nucleating agents in the enantioselective crystallization of an amino acid conglomerate system.